2013
DOI: 10.1371/journal.pbio.1001489
|View full text |Cite
|
Sign up to set email alerts
|

A Force-Activated Trip Switch Triggers Rapid Dissociation of a Colicin from Its Immunity Protein

Abstract: A single-molecule force study shows that rapid dissociation of a high-affinity protein interaction can be triggered by site-specific remodelling of one protein partner, and that prevention of remodelling maintains avidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 60 publications
(95 reference statements)
2
35
0
Order By: Relevance
“…The presence of the TolC box sequence serves to weaken interhelical interactions within the T domain and could facilitate its conversion to a more extended conformation that could then enter TolC as described above. For the DNase colicin E9, it has been demonstrated that the application of very low forces (Ͻ20 pN) is sufficient to trigger the dissociation of its immunity protein, which has a K d (dissociation constant) in the femtomolar range (41). It can be postulated that some comparably weak interaction between colicin E1 and TolC triggers its release from its BtuB receptor and an unfolding that would allow binding to and passage through TolC so that the channel-forming domain reaches its ultimate target, the bacterial inner membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the TolC box sequence serves to weaken interhelical interactions within the T domain and could facilitate its conversion to a more extended conformation that could then enter TolC as described above. For the DNase colicin E9, it has been demonstrated that the application of very low forces (Ͻ20 pN) is sufficient to trigger the dissociation of its immunity protein, which has a K d (dissociation constant) in the femtomolar range (41). It can be postulated that some comparably weak interaction between colicin E1 and TolC triggers its release from its BtuB receptor and an unfolding that would allow binding to and passage through TolC so that the channel-forming domain reaches its ultimate target, the bacterial inner membrane.…”
Section: Discussionmentioning
confidence: 99%
“…DNase-specific Im proteins are small acidic inhibitors that bind to an exosite and inhibit colicin or pyocin activity indirectly by blocking substrate-binding [15]. Im proteins are known to dissociate from colicins at the cell surface in a pmf-dependent step by a process that is thought to involve structural remodeling of the nuclease [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule force spectroscopy is a commonly used tool for the mechanical characterization of polymers and biological molecules, such as proteins and DNA [1][2][3][4][5][6][7][8][9][10], and ligand-protein interactions [11][12][13][14][15][16][17][18][19]. These experiments can be performed using a variety of experimental setups, including optical tweezers [3,20], the atomic force microscope (AFM) [1,4], magnetic tweezers [21,22], and the biomembrane force probe [23].…”
Section: Introductionmentioning
confidence: 99%